2012
DOI: 10.1111/j.1365-2095.2012.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inulin and fructooligosaccharides on growth performance, body chemical composition and intestinal microbiota of farmed rainbow trout (Oncorhynchus mykiss)

Abstract: The objectives of the present study were to investigate the effects of inulin and fructooligosaccharides (FOS) on growth performance, whole body and fillet chemical composition and intestinal microbiota of rainbow trouts reared under fish farming conditions. Trouts fed inulinor FOS-containing diets (5 and 10 g kg À1 ) exhibited significant (P = 0.030) body weight gain improvements compared with controls. An increase in gross energy (P = 0.044) and Ca content (P = 0.034) in the whole body of trouts was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 30 publications
8
59
3
3
Order By: Relevance
“…The improved growth response observed in the present study was similar to that reported previously in various fish species, including Nile tilapia, Siberian sturgeon (Acipenser baerii), and rainbow trout (Oncorhynchus mykiss) (Mahious et al, 2006a;Ibrahem et al, 2010;Ortiz et al, 2013). However, dietary supplementation with inulin did not affect the growth response in weaning turbot (Psetta maxima), Atlantic salmon (Salmo salar), hybrid striped bass (Morone chrysops x Morone saxatilis) (Mahious et al, 2006b;Bakke-McKellep et al, 2007;Burr et al, 2010), and it had a negative effect on the growth response in beluga (Huso huso) (Reza et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The improved growth response observed in the present study was similar to that reported previously in various fish species, including Nile tilapia, Siberian sturgeon (Acipenser baerii), and rainbow trout (Oncorhynchus mykiss) (Mahious et al, 2006a;Ibrahem et al, 2010;Ortiz et al, 2013). However, dietary supplementation with inulin did not affect the growth response in weaning turbot (Psetta maxima), Atlantic salmon (Salmo salar), hybrid striped bass (Morone chrysops x Morone saxatilis) (Mahious et al, 2006b;Bakke-McKellep et al, 2007;Burr et al, 2010), and it had a negative effect on the growth response in beluga (Huso huso) (Reza et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Instead, they are fermented in the large intestine or colon by beneficial bifidobacteria and other lactic acid producing bacteria, thereby enhancing their relative populations (Pool-Zobel et al, 2002;Roberfroid, 2002;Flickinger et al, 2003). Several dietary grades of inulin are available commercially, and their use as a dietary supplement in animal feed has been shown to enhance growth performance, modulate intestinal microbiota, and improve hematological and immune parameters in fish, poultry, and swine (He et al, 2002;Mahious et al, 2006a;Reza et al, 2009;Ibrahem et al, 2010;Mourino et al, 2012;Nabizadeh, 2012;Ortiz et al, 2013). Nevertheless, the use of inulin as a functional feed additive in the animal feed industry is limited by the cost of the inulin extraction process.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, there were no published studies showing improvement in gut morphology with inulin supplementation. As inulin could modulate fish gut bacterial community (Burr et al 2010;Ortiz et al 2013), it could be possible that inulin stimulates fish growth solely by modifying gut bacterial population in intestine of grass carp. Nevertheless, the exact mechanism behind the growth-promoting effect of prebiotic fibers on grass carp is not known and should be a topic of further study as various fish species responded differently to dietary prebiotic fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of prebiotics on growth performance are dependent on aspects such as prebiotic source, fish species and diet composition, which may explain why some studies reported improved fish growth due to dietary FOS incorporation (Mahious et al 2006;Zhou et al 2010;Soleimani et al 2012;Ortiz et al 2013;Wu et al 2013) while others reported no growth improvement (Grisdale-Helland et al 2008;Buentello et al 2010;Ye et al 2011;Hoseinifar et al 2014;Guerreiro et al 2014aGuerreiro et al , 2015b, or even report adverse effects on fish performance (Hoseinifar et al 2011a). In the present study, effect of dietary scFOS supplementation seems to be influenced by temperature.…”
Section: Discussionmentioning
confidence: 94%
“…Among prebiotics, fructooligosaccharides (FOS) are one of the most tested in fish (Merrifield et al 2010;Ringø et al 2010Ringø et al , 2014Dimitroglou et al 2011;Hoseinifar et al 2014;Zhang et al 2014). However, studies conducted so far in fish have been focused mainly on FOS effects on growth performance, immune response and disease resistance (Grisdale-Helland et al 2008;Buentello et al 2010;Ai et al 2011;Ye et al 2011;Soleimani et al 2012;Ortiz et al 2013;Wu et al 2013;Zhang et al 2013Zhang et al , 2014Hoseinifar et al 2014;Guerreiro et al 2014aGuerreiro et al , b, 2015b. To our knowledge, up to now only two studies aimed to access short-chain fructooligosaccharides (scFOS) effects on fish metabolism (Guerreiro et al 2014a(Guerreiro et al , 2015b.…”
Section: Introductionmentioning
confidence: 96%